The first 100 days of SARS-CoV-2 control in Vietnam - Pham, QT; Rabaa, MA; Duong, HL; Dang, QT; Tran, DQ; Quach, H-L; Hoang, N-AT; Phung, CD; Ngu, DN; Tran, AT; La, NQ; Tran, MP; et al. (Oxford University Press, 2020)
Background: One hundred days after SARS-CoV-2 was first reported in Vietnam on January 23rd, 270 cases were confirmed, with no deaths. We describe the control measures used by the Government and their relationship with imported and domestically-acquired case numbers, with the aim of identifying the measures associated with successful SARS-CoV-2 control.